The factors affecting the interpretation of geochemical surveys in mineral exploration - Fletcher, B A (Rhodes University, Faculty of Science, Department of Geology, 1982)
[From introduction] Exploration geochemistry is an indirect method of detecting mineral deposits by measuring the abundance and distribution of ore elements and elements closely associated with ore in natural materials at or near the earth's surface. The method relies on the assumption that a mineral deposit is reflected by unusual element abundances or distribution patterns (geochemical halos), and that these indications of mineralization can be detected by geochemical surveys involving the collection and analysis of natural materials. The interpretation of geochemical surveys in mineral exploration involves: 1) The use of geological and statistical inference, based on a knowledge of the normal behaviour and distribution of indicator elements in the exploration area, to recognize apparent geochemical anomalies in field and analytical data and to predict the type of geochemical halo reflected by the anomalies. 11) The use of geological inference, based on a knowledge of the characteristics of geochemical halos and their relationship to mineral deposits, to predict the presence and probable location of an ore body. The interpretation process is, however, complicated by the absence of a simple universal formula that relates the abundance and distribution of elements in natural materials to the presence or absence of a mineral deposit. The interpretation of a geochemical survey must, thus, be based on an empirical approach which avaluates each survey as an individual problem. The objective of this dissertation is to illustrate the factors affecting the "nuts and bolts" approach to the interpretation of geochemical surveys in mineral exploration. The discussion is aimed at providing field geologists responsible -for the planning and execution of geochemical surveys with some basic guidelines for interpreting the surveys. I hope that the contents of this dissertation will help field geologists to "look in the last place first".
Keywords: Geochemistry; Geochemistry -- Environmental aspects; Mining geology; Minerals; Ore deposits; Geochemical prospecting